COMPARATIVE ANALYSIS OF CLASSICAL AND AGILITY PROJECT MANAGEMENT METHODOLOGIES - Sattarova Nargiza Toxirovna; Mamatazimov Jaloliddin Sherzod o’g’li (TADQIQOTLAR, 2025)
Abstract: Our article provides a comparative analysis of classic and agile project management methodologies. We examine the key principles, features, advantages, and disadvantages of each methodology. Particular attention is paid to practical aspects of application, including choosing the appropriate methodology based on the nature of the project, the stability of requirements, and the characteristics of the team.